2019
DOI: 10.1029/2018ja025674
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Response to the St. Patrick's Day Space Weather Events in March 2012, 2013, and 2015 at Southern Low and Middle Latitudes

Abstract: The changes in critical frequency of the F2 layer (foF2) and foF2 deviation (ΔfoF2) have been determined for three geomagnetic storms in March of the years 2012, 2013, and 2015 at low‐latitude stations, Darwin (geomag. lat. 21.96°S) and Townsville (28.95°S), and midlatitude stations, Brisbane (36.73°S), Canberra (45.65°S), and Hobart (54.17°S). The moderate storm during 15–16 March 2012 (Dst = −87 nT) showed a decrease in foF2 at midlatitude and no effect at low‐latitude stations. For the intense storm of 17–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…This storm was second largest geomagnetic storm of the solar cycle 24 after the March 17–18 storm in 2015. It was associated with two CMEs that hit the Earth environment on June 22 (S. Kumar & Kumar, 2019). The IMF B z sharply varied between positive (northward) and negative (southward) values.…”
Section: Resultsmentioning
confidence: 99%
“…This storm was second largest geomagnetic storm of the solar cycle 24 after the March 17–18 storm in 2015. It was associated with two CMEs that hit the Earth environment on June 22 (S. Kumar & Kumar, 2019). The IMF B z sharply varied between positive (northward) and negative (southward) values.…”
Section: Resultsmentioning
confidence: 99%
“…It indicated that the positive and negative mechanisms coexisted and competed to each other. The relative contribution varied with location, local time, storm phase, and other factors (Kumar & Kumar, 2019; Liu et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The geomagnetic storms are the disturbances of the Earth's magnetic field, and the impact of solar wind particles enhancement (Buonsanto, 1999; Gonzalez et al., 1994; Kumar & Kumar, 2019). Following geomagnetic storms, the ionosphere also has obvious disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the empirical high‐latitude drivers of convection and auroral precipitation could yield a pattern smoother than reality, particularly during geomagnetic storms. Although Wuhan is located at low geomagnetic latitude, the mid‐ and low‐latitude ionosphere could also be affected by geomagnetic storms (e.g., Kumar, S., & Kumar, V. V., 2019). This result is supported by the comparison between Figure 7c and 7d that the SD‐WACCM‐X simulated variability is also different from observations under “disturbed” conditions.…”
Section: Discussionmentioning
confidence: 99%